Heterogeneous Fundamentalists in a Continuous Time Model with Delays - Luca Gori; Luca Guerrini; Mauro Sodini (Discrete Dynamics in Nature and Society)
We develop a continuous time model with heterogeneous fundamentalists, imitators, and discrete time delays. We show that nonlinear dynamic phenomena, such as coexistence of attractors and local and global bifurcations, occur due to the existence of a time gap in the process of adjustment of market prices.